EFEKTIVITAS PROGRAM GERAKAN MEMBANGUN EKONOMI RAKYAT LAMONGAN BERBASIS PEDESAAN - Nur Kholilatul Maulidiyah; Tukiman Tukiman (Jurnal Penelitian Administrasi Publik, 2021)
This research is based on the phenomenon of the rural-based Lamongan people's economic development movement program, by providing assistance in agriculture, namely Alsintan (handtractors. The existence of a movement program to build a rural-based Lamongan people's economy is expected to be able to provide economic improvements to the people of Lamongan, especially those in rural areas by developing potential the potential is available in every village, with the assistance of alsintan in the form of village community handtractors, they have the opportunity to improve their quality of life, especially to improve the economy, and to carry out a program to develop rural-based Lamongan people's economy, namely to reduce poverty in the Lamongan Regency with a target of 12% in in 2021. This type of research is descriptive qualitative. The location of this study is in the Village Lawanganagung Sugio District Lamongan Regency. The focus of this research is based on the theory of Budiani (2007) cited by Amrizal, Dalimunthe, and Yusriati (2018: 59) namely (1) accuracy of program objectives, (2) program socialization, (3) program objectives, and (4) program monitoring. Data collection techniques by observation, interview, and documentation. The results obtained from this study are (1) the accuracy of the program targets, to determine the targets in the rural-based Lamongan people's economic development movement program that is on target and is effective, namely the active farmer groups. (2) program socialization, in the rural-based Lamongan people's economic development program movement has been effective and good, in accordance with information received by farmer groups by submitting the conditions for requesting proposals, how to use hand tractors and how to care for them. (3) program objectives, with the implementation of the rural-based Lamongan people's economic development movement program aimed at improving the economy of rural communities with faster processing of land tractors and reducing costs, so that rice productivity increases. (4) program monitoring, for the rural-based Lamongan people's economic development movement program has been effective, all agencies carry out monitoring / supervision / monitoring for the hand tractor assistance. Keyword: effectiveness, GEMERAP program